Heterogeneous Fog Generated with the E ect of Light Scattering and Blur - Gawron, Michał; Boryczka, Urszula (Wydawnictwo Politechniki Łódzkiej, 2018)
The development of computer graphics forces new requirements on the developers, which will make the virtual world more similar to the real world. One of these elements is the simulation of fog. Common fog algorithms mix the color of the scene with the color of the fog over a certain distance. However, one feature of the naturally foggy scenery is ignored. With the distance and density of the fog, the observed scenery or individual objects become more blurred. In this paper we will present our implementation of the distance fog in the Unreal Engine 4, including the effect of blurring the foggy areas, simulating of light scattering and variations in fog density using noise.
Keywords: computer graphics; computer games; fog; blur; Unreal Engine; grafika komputerowa; gry komputerowe; mgła; rozmycie